2004
DOI: 10.3200/psfl.48.3.24-34
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Involving Parents of Children With Learning and Behavior Problems in the Schools

Abstract: The authors present a practical model for including parents of children with learning and behavior problems in the schools. First, characteristics of families with children with learning and behavior problems are discussed. Next, 4 features of an effective program to involve parents are presented. These features are: (a) proactive design, (b) 180-day plan for the school year, (c) clear goals and expectations, and (d) accommodation of diverse families. Our model for including parents has 4 phases. Phase 1: Prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
1
18
0
4
Order By: Relevance
“…In this article and others previously mentioned, Darch et al (2004) stated that parental involvement led to increased student achievement in school, higher test performance, more consistent attendance, higher rates of homework completion, higher grades, increased motivation and more positive attitudes towards school activities. They identified some of the strategies that could be used to engage parents of these children such as providing behavioral techniques to be used at home with reinforcement, parental support in the classroom and reinforcement of social skills taught at school.…”
Section: Culturally and Linguistically Diverse Communitiesmentioning
confidence: 91%
“…In this article and others previously mentioned, Darch et al (2004) stated that parental involvement led to increased student achievement in school, higher test performance, more consistent attendance, higher rates of homework completion, higher grades, increased motivation and more positive attitudes towards school activities. They identified some of the strategies that could be used to engage parents of these children such as providing behavioral techniques to be used at home with reinforcement, parental support in the classroom and reinforcement of social skills taught at school.…”
Section: Culturally and Linguistically Diverse Communitiesmentioning
confidence: 91%
“…A school-wide communication system that serves as a consistent and predictable communication resource for African American parents is important. This may take the form of a parent handbook that addresses questions commonly asked by parents regarding special education and other matters, a calendar of parent conferences provided at the beginning of the year, or a school Web site that contains pertinent information that is updated weekly or monthly (Darch, Miao, & Shippen, 2004). When empowering parents through communication, educators must work to meet the unique needs of the parents with whom they work.…”
Section: Suggestions For Increasing African American Involvement In Smentioning
confidence: 98%
“…Researchers (Darch, Miao, & Shippen, 2004;Howland, Anderson, Smiley, & Abbott, 2006;Spann, Kohler, & Soenksen, 2003) have indicated that family involvement is related to increased academic achievement, sustained positive attitudes toward school (Brandon, 2007), and improved attendance (Darch et al, 2004). Researchers (Darch, Miao, & Shippen, 2004;Howland, Anderson, Smiley, & Abbott, 2006;Spann, Kohler, & Soenksen, 2003) have indicated that family involvement is related to increased academic achievement, sustained positive attitudes toward school (Brandon, 2007), and improved attendance (Darch et al, 2004).…”
Section: Increasing Family Involvement In Schoolsmentioning
confidence: 99%